Persistence of livestock-associated antibiotic-resistant Staphylococcus aureus among industrial hog operation workers in North Carolina over 14 days. Issue 2 (8th September 2014) - Nadimpalli, Maya; Rinsky, Jessica L; Wing, Steve; Hall, Devon; Stewart, Jill; Larsen, Jesper; Nachman, Keeve E; Love, Dave C; Pierce, Elizabeth; Pisanic, Nora; Strelitz, Jean; Harduar-Morano, Laurel; et al.
Abstract : Objectives: This study aimed to evaluate the persistence of nasal carriage of Staphylococcus aureus, methicillin-resistant S. aureus and multidrug-resistant S. aureus over 14 days of follow-up among industrial hog operation workers in North Carolina. Methods: Workers anticipating at least 24 h away from work were enrolled June–August 2012. Participants self-collected a nasal swab and completed a study journal on the evening of day 1, and each morning and evening on days 2–7 and 14 of the study. S. aureus isolated from nasal swabs were assessed for antibiotic susceptibility, spa type and absence of the scn gene. Livestock association was defined by absence of scn . Results: Twenty-two workers provided 327 samples. S. aureus carriage end points did not change with time away from work (mean 49 h; range >0–96 h). Ten workers were persistent and six were intermittent carriers of livestock-associated S. aureus. Six workers were persistent and three intermittent carriers of livestock-associated multidrug-resistant S. aureus . One worker persistently carried livestock-associated methicillin-resistant S. aureus . Six workers were non-carriers of livestock-associated S. aureus . Eighty-two per cent of livestock-associated S. aureus demonstrated resistance to tetracycline. A majority of livestock-associated S. aureus isolates (n=169) were CC398 (68%) while 31% were CC9. No CC398 and one CC9 isolate was detected among scn- positive isolates. Conclusions: Nasal carriage of livestock-associated S. aureus, multidrug-resistant S. aureus and methicillin-resistant S. aureus can persist among industrial hog operation workers over a 14-day period, which included up to 96 h away from work.